Absceso Espinal Epidural secundario a bloqueo terapéutico: Presentación de un caso Epidural spinal abscess secondary to therapeutic blockade: Presentation of a case - Nereida Rosa Estorino Escaig; Eligio Vidal Jiménez; Crecencio Aneiro Alfonso (Revista Médica Electrónica, 2010)
The epidural spinal abscess is a purulent collection located between the dura mater and the rachimedular duct, being an unusual entity but a devastating situation, and causing a high morbimortality if it is not followed adequately. It is originated by direct extension (contiguity, local invasive procedures) or by dissemination from distant infectious focuses (hematogenic way). It has an incidence of 1 per 10 000 patients, with a bigger incidence in the third age (sixth decade), but without obviating the others, including childhood with literature reports of more than 90 cases; with the advent of drugs used endovenously, there is an increasing tendency in young population, and also a predominance of the male sex. It is low incidence pathology; fever and dorsolumbalgy are the most frequent symptoms, followed by radicular distributed pain, associated to motor deficit and anal and vesical sphincter disturbances. Occasionally it can develop a septic picture that reaches even a septic shock. The selected study is the magnetic resonance with gadolinium.